2009
DOI: 10.1093/sleep/32.11.1449
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Effects of Sleep During the First Year of Life on Cognitive, Psychomotor, and Temperament Development

Abstract: During the first year of life, infants spend most of their time in the sleeping state. Assessment of sleep during infancy presents an opportunity to study the impact of sleep on the maturation of the central nervous system (CNS), overall functioning, and future cognitive, psychomotor, and temperament development. To assess what is currently known regarding sleep during infancy and its effects on cognitive, psychomotor, and temperament development, we assessed the relevant literature published over the last sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
145
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(151 citation statements)
references
References 71 publications
2
145
0
4
Order By: Relevance
“…PI present sleep with polyphasic pattern that are classified into three stages: active, quiet and indeterminate sleep (3,7,(9)(10) . The different stages of sleep are essential for the homeostasis of premature infants, because they establish relations with important physiological and neurological activities (3,9) . In the quiet sleep, decreased basal metabolic rate occurs, which promotes replenishment of energy reserves as well as promote cellular repair, in the active sleep brain activation occurs, which is essential for the structural maturation of the central nervous system (10)(11) .…”
mentioning
confidence: 99%
“…PI present sleep with polyphasic pattern that are classified into three stages: active, quiet and indeterminate sleep (3,7,(9)(10) . The different stages of sleep are essential for the homeostasis of premature infants, because they establish relations with important physiological and neurological activities (3,9) . In the quiet sleep, decreased basal metabolic rate occurs, which promotes replenishment of energy reserves as well as promote cellular repair, in the active sleep brain activation occurs, which is essential for the structural maturation of the central nervous system (10)(11) .…”
mentioning
confidence: 99%
“…[1] Thus, the relationship between the two is vital, as the control of sleepwake cycles are regulated by the CNS. [2] At present, we do not have sufficient data to conclude that a causal relationship exists between infant's sleep and development. The EEG recording itself is quite different in children than adults because the brain, meninges, skull, scalp, head size as well as child's behavior, and ability to cooperate all changes over time.…”
Section: Introductionmentioning
confidence: 87%
“…Clinical studies with infants younger than 12 months showed associations between sleep duration, number of awakenings and sleep morphology in EEG with concurrent and later scores in standardised developmental batteries (Becker & Thoman, 1981;Freudigman & Thoman, 1993;Scher, Steppe, & Banks, 1996; for a review see Ednick et al, 2009). Longitudinal relationships across longer periods of development have also been found for toddlers (Dearing, McCartney, Marshall, & Warner, 2001) and school-aged children (Buckhalt, El-Sheikh, & Keller, 2007;Buckhalt, El-Sheikh, Keller, & Kelly, 2009).…”
Section: Introductionmentioning
confidence: 98%